Triathlon & Endurance Sports - Kruseman M; 2; Lecoultre V; Gremeaux V; 4 (Deutsche Zeitschrift für Sportmedizin)
Long distance triathlon (i.e. half- or full ironman distances) brings specific nutritional challenges and extra attention is necessary for optimal fueling when training six to eighteen hours weekly, especially among age-group athletes who juggle training, work and family life.In the first section of this narrative review we discuss optimal body weight and energy availability, the instances where carbohydrates or fats should be preferred during training, the effects of high-fat/low-carb diets and the role of protein, micronutrients and ergogenic supplements in endurance sports.The second part of this paper describes optimal nutrition and hydration strategies for racing. The specific format of the race necessitates careful planning of food and fluid intake to meet the large amounts of energy required to complete a full or half-ironman triathlon.Most of the refueling takes place on the bicycle, which has a longer duration but also offers the opportunity to chew and drink properly while in a seated position. Gastrointestinal distress affects 14-30% of triathletes, and training the gut is of utmost importance to allow for sufficient food and fluid intake. Indeed, entering the run in a depleted nutritional state will most likely force the athlete to slow down in order to finish the race. Key Words: Endurance Sports, Body Weight, Carbohydrates, Fats, Hydration